Experimental studies on the thickness of upward flame over poly(methyl methacrylate) slabs. (31st July 2017) - Zhou, Jin; Mao, Jinfeng; Han, Xu; Xing, Zheli; Deng, Zhongkai
Summary: Experiments were performed to investigate the flame thickness of the upward flame on the poly(methyl methacrylate) slabs with width of 100‐400 mm. The results indicated that the flame thickness exhibited an increase first and then decrease trend in the upright orientation, and the maximum thickness location was approximately equal to the pyrolysis front location. The thickness of the flame along the lateral side of slab was less than that of the interior flame. The flame maximum thickness as a function of pyrolysis height and width was obtained, which showed the maximum thickness provided a power law increase with the pyrolysis height and width. Furthermore, the maximum thickness exhibited a power law increase with the total heat release rate as well. Based on the obtained flame thickness, the radiation heat flux at the pyrolysis height was estimated by using a simplified model. Comparison with the calculated convective heat flux revealed approximated pyrolysis heights for upward flame transition from convective heat flux controlled to radiation heat flux controlled.